Hydrogen peroxide attenuates the dipsogenic, renal and pressor responses induced by cholinergic activation of the medial septal area. (22nd January 2015) - Melo, M.R.; Menani, J.V.; Colombari, E.; Colombari, D.S.A.
Highlights: Cholinergic activation of MSA with carbachol induces thirst, natriuresis, antidiuresis and pressor response. Carbachol injected into the MSA also increases c-Fos expression in vasopressinergic and oxytocinergic neurons of the PVN. H2 O2 acting through K + ATP channels in the MSA inhibits responses induced by cholinergic activation in the same area. Abstract: Cholinergic activation of the medial septal area (MSA) with carbachol produces thirst, natriuresis, antidiuresis and pressor response. In the brain, hydrogen peroxide (H2 O2 ) modulates autonomic and behavioral responses. In the present study, we investigated the effects of the combination of carbachol and H2 O2 injected into the MSA on water intake, renal excretion, cardiovascular responses and the activity of vasopressinergic and oxytocinergic neurons in the hypothalamic paraventricular (PVN) and supraoptic (SON) nuclei. Furthermore, the possible modulation of carbachol responses by H2 O2 acting through K + ATP channels was also investigated. Male Holtzman rats (280–320 g) with stainless steel cannulas implanted in the MSA were used. The pre-treatment with H2 O2 in the MSA reduced carbachol-induced thirst (7.9 ± 1.0, vs. carbachol: 13.2 ± 2.0 ml/60 min), antidiuresis (9.6 ± 0.5, vs. carbachol: 7.0 ± 0.8 ml/120 min, ), natriuresis (385 ± 36, vs. carbachol: 528 ± 46 μEq/120 min) and pressor response (33 ± 5, vs. carbachol: 47 ± 3 mmHg). Combining H2 O2 and carbachol into the MSA also reduced the number of vasopressinergic neurons expressing c-Fos in the PVN (46.4 ± 11.2, vs. carbachol: 98.5 ± 5.9 c-Fos/AVP cells) and oxytocinergic neurons expressing c-Fos in the PVN (38.5 ± 16.1, vs. carbachol: 75.1 ± 8.5 c-Fos/OT cells) and in the SON (57.8 ± 10.2, vs. carbachol: 102.7 ± 7.4 c-Fos/OT cells). Glibenclamide (K + ATP channel blocker) into the MSA partially reversed H2 O2 inhibitory responses. These results suggest that H2 O2 acting through K + ATP channels in the MSA attenuates responses induced by cholinergic activation in the same area.